wikhikhotuwok and the Re-Storying of Menahkwesk: Telling History Through Treaty - Brooks, Gina; Bryant, Rachel (Journal of New Brunswick Studies / Revue d’études sur le Nouveau-Brunswick, 2024)
This article is based on a basket installation created for the 2022 Arts Atlantic Symposium. The work of forging active relationships in the spirit of the Peace and Friendship Treaties has both significant challenges and transformative implications in Menahkwesk (Saint John). We collaborated on two birchbark baskets that can hold the history of Menahkwesk and that model and explain our understandings of the relationships that Saint John was violently consolidated against in 1785. We honour principles from the Wolastoqey Latuwewakon in the structure of our collaboration, along with the fact that the first gift that Gluscap gave the Wolastoqiyik was the bark that would take care of the people. In this article, we show and discuss how the creative actions of treaty (and not just the language of treaty) allow us to share visions of the past while simultaneously envisioning a shared future.